IRREGULAR SLEEP PATTERNS AND THEIR ASSOCIATION WITH HYPERTENSION RISK AMONG INFORMAL SECTOR WORKERS: A COMMUNITY-BASED STUDY - Arif Wicaksono; Intan Nur Aini; Nova Naila Shaqira (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Background: Hypertension remains a major public health challenge, and irregular sleep patterns have emerged as a modifiable behavioral risk factor associated with elevated blood pressure, particularly among informal workers. Objective: This study aimed to analyze the effect of irregular sleep patterns on the incidence of hypertension among agricultural workers in Watugaluh Village, Diwek District, Jombang Regency. Methods: A quantitative analytic study with a cross-sectional design was conducted involving 96 agricultural workers selected through purposive sampling. Sleep patterns were assessed using a structured questionnaire, while blood pressure was measured using a validated digital sphygmomanometer. Data were analyzed using descriptive statistics, Chi-square test, and binary logistic regression with a significance level of 0.05. Results: Most respondents were middle-aged male workers, with 39.6% experiencing irregular sleep patterns and 40.6% diagnosed with hypertension. Chi-square analysis demonstrated a significant association between irregular sleep patterns and hypertension (χ² = 13.911; p = 0.00019). Binary logistic regression further confirmed that sleep pattern was a significant predictor of hypertension (β = −0.205; OR = 0.815; p < 0.001), indicating that improved sleep regularity reduced the likelihood of hypertension by approximately 18.5%. Conclusion: Irregular sleep patterns significantly influence hypertension among agricultural workers. Integrating sleep pattern assessment and sleep hygiene education into community-based hypertension prevention programs may strengthen early detection and reduce cardiovascular risk in informal worker populations.